An insight into genetic landscape of inflammatory bowel disease - Baig, Zunaira Ali; Majeed, Asifa (Journal of the Pakistan Medical Association, 2023)
Inflammatory bowel disease has been regarded to be chronic intestinal inflammation characterised by a dsyregulatory immune response. The disease pathophysiology is known to be complex. Growing pieces of evidences underpin the involvement of various environmental and genetic determinants in the disease onset. The current narrative review was planned to manifest the contribution of genetic drivers for disease onset and to target signalling pathways that might present a therapeutic potential for further research. The factors of the disease that provide the genetic nature and understanding of the pathways involved have been researched in recent times. Also, numerous disease-developing factors have been studied and assessed. Among them genetic determinants of disease onset have further improved the understanding of disease development. Genetic contributors to the onset of disease as well as important therapeutic targets need to be understood as predictive genetic risk factors have a potential implication for personalised treatment.